Calcium silicate hydrate nano material as well as preparation method and application thereof

Through the combination of hydrated calcium silicate nanomaterials and CTAB, the problems of high cost and low efficiency of CO2 capture in the prior art are solved, and efficient carbon capture at low CO2 concentration is achieved, providing a low cost and performance Excellent direct carbon capture material.

CN119215848APending Publication Date: 2024-12-31SOUTHEAST UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411348432.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing CO2 capture technology is costly and inefficient at low CO2 concentrations. In particular, the direct air capture method has increased investment in capture materials and energy demand due to the thin carbon dioxide concentration, which limits its wide application.

Method used

Rod-shaped or block-shaped calcium silicate nanomaterials are prepared by combining solute hydrated calcium silicate and cetyltrimethylammonium bromide (CTAB) in the total solvent system. The material can achieve efficient carbon capture at low CO2 concentration, combine CTAB as a surfactant to regulate nanostructures and improve capture efficiency.

Benefits of technology

It has achieved efficient carbon capture at a concentration of as low as 0.03%, with a proportion of capture mass of 26%, low material cost, simple preparation method, and commercial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215848A_ABST
    Figure CN119215848A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrated calcium silicate nano material as well as a preparation method and application thereof. The hydrated calcium silicate nanostructure material comprises hydrated calcium silicate (C-S-H) and cetyltrimethylammonium bromide (CTAB), the mass percent of the CTAB in a total solvent system is greater than 0 and less than or equal to 0.025 g / mL, and the mole percent of the CSH in the total solvent system is 0.8-1.2 mol / L. According to the hydrated calcium silicate nano material, low-cost direct carbon capture is realized, capture can be quickly carried out in an environment with relatively low carbon dioxide concentration, and the hydrated calcium silicate nano material is simple to prepare and stable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a calcium silicate hydrate nano material and a preparation method and application thereof, belonging to the field of direct carbon capture. Background Art

[0002] The use of fossil fuels helps to advance the industrialization process and meet people's living needs, but as a non-renewable energy, fossil energy not only causes energy depletion, but also emits a large amount of CO2 gas during the combustion process, causing a series of serious hazards such as the greenhouse effect.

[0003] Carbon capture, utilization, and storage (CCUS) technology primarily involves three steps: CO2 capture, CO2 utilization, and CO2 storage. CO2 capture is the core step, also characterized by high energy consumption and cost. Improving capture efficiency and reducing capture costs are current international research hotspots. CO2 capture technologies can be categorized by capture method, including absorption, adsorption, membrane separation, and novel CO2 capture technologies. Liquid absorption has achieved commercialization, while traditional amine solvents, due to their excellent CO2 solubility and rapid absorption rate, have become a relatively mature CO2 capture method for industrial applications. However, amine solvents suffer from high solvent volatilization losses and severe equipment corrosion, resulting in high investment and operating costs, severely limiting their widespread adoption. Other CO2 capture technologies still require further advancement in maturity. For example, solid adsorption is still in the industrial demonstration stage, while membrane separation, chemical looping combustion, and direct air capture are in the pilot stage, and electrochemical capture is in the basic research stage. Direct air capture (DAC) refers to a technology that captures CO2 directly from the atmosphere. It uses specific chemical or physical methods to separate CO2 from the air for storage or utilization. DAC can directly capture carbon at lower CO2 concentrations. Its wide range of applications and low operating conditions make it a major research hotspot.

[0004] The CO2 concentration in DAC directly impacts capture costs; higher concentrations mean lower costs. The CO2 concentration in natural air is much lower than in industrial flue gas, making the capture environment more uncontrollable. This makes DAC not only technically challenging, but also requires high investment in capture materials and energy. Therefore, developing a low-cost capture agent with a wide range of CO2 concentrations is crucial to advancing DAC technology. Summary of the Invention

[0005] Objectives of the Invention: To address the problems existing in the prior art, the first objective of the present invention is to provide a low-cost calcium silicate hydrate nanomaterial capable of direct carbon capture at relatively low CO₂ concentrations. A second objective is to provide a method for preparing this calcium silicate hydrate nanomaterial. A third objective is to provide applications of this calcium silicate hydrate nanomaterial in carbon capture. This calcium silicate hydrate nanomaterial is simple to prepare, requires mild conditions, and is capable of direct carbon capture at concentrations as low as CO₂ in air.

[0006] Technical solution: The present invention provides a calcium silicate hydrate nanomaterial, which includes a solute calcium silicate hydrate (CSH) and a total solvent system, wherein the total solvent system contains cetyltrimethylammonium bromide (CTAB), wherein the molar percentage of calcium silicate hydrate to the total solvent system is 0.8 to 1.2 mmol / mL, and the solid-to-liquid ratio X of cetyltrimethylammonium bromide to the total solvent system is 0<X≤0.030 g / mL.

[0007] Furthermore, the molar percentage of calcium silicate hydrate to the total solvent system is 1.0 mmol / mL, and the solid-to-liquid ratio X of hexadecyltrimethylammonium bromide to the total solvent system is 0.005≤X≤0.025 g / mL.

[0008] Furthermore, the calcium silicate hydrate nanomaterial is in the shape of rods or blocks.

[0009] Furthermore, when the solid-liquid ratio X of hexadecyltrimethylammonium bromide to the total solvent system is 0.0125<X≤0.030 g / mL, the calcium silicate hydrate nanomaterial is rod-shaped, preferably 0.015≤X≤0.030 g / mL, more preferably 0.025 g / mL.

[0010] Furthermore, when the solid-to-liquid ratio X of hexadecyltrimethylammonium bromide to the total solvent system is about 0.0125 g / mL, the calcium silicate hydrate nanomaterial is in a transitional state between rods and blocks.

[0011] Furthermore, when the solid-liquid ratio X of hexadecyltrimethylammonium bromide to the total solvent system is 0<X<0.0125 g / mL, the calcium silicate hydrate nanomaterial is in block form, preferably 0<X≤0.010 g / mL, more preferably 0.005 g / mL.

[0012] A method for preparing the calcium silicate hydrate nanomaterial of the present invention comprises the following steps:

[0013] (1) adding sodium silicate and CTAB to the solution from which carbon dioxide has been removed, performing ultrasonic dispersion, and heating and stirring under nitrogen protection to obtain a sodium silicate mixed solution;

[0014] (2) adding CaCl2 to the sodium silicate mixed solution and heating under reflux for reaction;

[0015] (3) adding ammonia water to the solution obtained in step (2) to adjust the pH, collecting the precipitate by centrifugation, and freeze-drying to obtain a hydrated calcium silicate material.

[0016] Furthermore, in step (1), the solution is water or a solution containing water.

[0017] Furthermore, in step (1), the ultrasonic dispersion time is more than 10 minutes.

[0018] Furthermore, in step (1), the heating and stirring is heating to 50-80°C and stirring at 800-1200 rpm for more than 0.5 h, preferably 70°C.

[0019] Furthermore, in step (2), the CaCl2 added is CaCl2 solid or CaCl2 aqueous solution from which carbon dioxide has been removed.

[0020] Furthermore, in step (2), the molar ratio of CaCl2 to sodium silicate is 1 to 2:1.

[0021] Furthermore, in step (2), the heating reflux reaction is carried out at 60-80° C. and 800-1200 rpm for 4-8 hours.

[0022] Furthermore, in step (3), the pH is adjusted to 11-14.

[0023] Furthermore, in step (3), the freeze-drying temperature is -30 to -50°C, and the freeze-drying time is 6 to 12 hours.

[0024] The present invention also includes the use of the calcium silicate hydrate nanomaterial in direct carbon capture.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0026] (1) The calcium silicate hydrate material provided by the present invention is prepared from calcium chloride, sodium silicate, and CTAB. The preparation method is simple and flexible, and the cost is low, and it can be applied to commercial direct carbon capture materials;

[0027] (2) The direct carbon capture hydrated calcium silicate material provided by the present invention has good performance, is non-toxic and can exist and operate stably;

[0028] (3) The direct carbon capture calcium silicate hydrate material provided by the present invention fully combines the nanostructure regulation of CSH by CTAB as a surfactant, and can capture carbon in a wide capture range as low as 0.03% carbon dioxide concentration, with a carbon capture mass ratio of up to 26%;

[0029] (4) The direct carbon capture hydrated calcium silicate material provided by the present invention can respond to normal carbon dioxide concentrations in the environment and has great application prospects in future commercial carbon capture materials due to its low price and simple preparation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Transmission electron micrographs of calcium silicate hydrate nanomaterials prepared in Examples 1-3 and Comparative Example 1; wherein, a is Comparative Example 1, b is Example 2, c is CTAB dosage of 0.010 g / mL in Example 3, d is CTAB dosage of 0.0125 g / mL in Example 3, e is CTAB dosage of 0.015 g / mL in Example 3, and f is Example 1;

[0031] Figure 2 The carbonization results of the hydrated calcium silicate nanomaterials prepared in Examples 1-3 and Comparative Example 1 are compared; wherein, a is a thermogravimetric test result diagram, and b is a comparison diagram of water content, CTAB ratio, and carbonization ratio. DETAILED DESCRIPTION

[0032] Example 1 Preparation of rod-shaped calcium silicate hydrate

[0033] This embodiment provides a method for preparing a rod-shaped calcium silicate hydrate nanomaterial, which specifically includes the following steps:

[0034] (1) Preparation of sodium silicate mixed solution: 0.3183 g of sodium silicate and 1 g of CTAB were placed in a 50 mL three-necked flask, 20 g of deionized water from which carbon dioxide had been removed was poured into the flask, and ultrasonicated for 10 min. After connecting a condenser, the mixture was evacuated and nitrogen was introduced. The mixture was heated in an oil bath to 70°C and stirred at 1200 rpm for 0.5 h until the CTAB was completely dissolved and became transparent, thereby obtaining a sodium silicate mixed solution.

[0035] (2) Preparation of calcium chloride solution: 0.1831 g of calcium chloride was placed in a 25 mL beaker, and 20 g of deionized water from which carbon dioxide had been removed was added. Ultrasonication was performed for 10 min to obtain a calcium chloride solution.

[0036] (3) Preparation of precursor rod-shaped CSH sol: Calcium chloride solution was added to the sodium silicate mixed solution, heated to 70°C in an oil bath at 1200 rpm and stirred for 6 h until the solution turned white. After the solution cooled to room temperature (24°C), ammonia water was added to the flask to adjust the pH to 12, and the mixture was collected by centrifugation to obtain a white rod-shaped CSH sol.

[0037] (4) Powder sample preparation: The precursor rod-shaped CSH sol is placed in a freeze drying oven, the freeze drying temperature is set to -40 °C, and the drying time is 12 h. After freeze drying, a rod-shaped calcium silicate hydrate material with direct carbon capture performance can be obtained.

[0038] In the rod-shaped direct carbon capture material CSH prepared in this example, the mass percentage of CTAB in the total solvent system is 0.025 g / mL, and the molar percentage of CSH in the total solvent system is 1 mmol / mL. Therefore, the rod-shaped calcium silicate hydrate material is recorded as CSH-0.025.

[0039] The rod-shaped calcium silicate hydrate material prepared in this example was analyzed by transmission electron microscopy, and the results were as follows: Figure 1 As shown in f. Figure 1 From the TEM image in middle f, it can be seen that the rod-shaped calcium silicate hydrate nanomaterial prepared with a CTAB concentration of 0.025 g / mL is rod-shaped.

[0040] Comparative Example 1

[0041] The experimental process is the same as step 1, except that CTAB is not used, and a flaky calcium silicate hydrate material is prepared, which is recorded as CSH-0.

[0042] The flaky calcium silicate hydrate material prepared in this comparative example was analyzed by transmission electron microscopy. The results are as follows: Figure 1 As shown in a. Figure 1 From the TEM image in (a), it can be seen that the CSH prepared without using CTAB (0 g / mL) is in the form of flakes.

[0043] Example 2 Preparation of massive calcium silicate hydrate

[0044] This embodiment provides a method for preparing a blocky calcium silicate hydrate nanomaterial. The experimental process is the same as that of Example 1, except that the amount of CTAB used is different. Specifically, the method includes the following steps:

[0045] (1) Preparation of sodium silicate mixed solution: 0.3183 g of sodium silicate and 0.2 g of CTAB were placed in a 50 mL three-necked flask, 20 g of deionized water from which carbon dioxide had been removed was poured into the flask, and ultrasonicated for 10 min. After connecting a condenser, the mixture was evacuated and nitrogen was introduced. The mixture was heated in an oil bath to 70°C and stirred at 1200 rpm for 0.5 h until the CTAB was completely dissolved and became transparent, thereby obtaining a sodium silicate mixed solution.

[0046] (2) Preparation of calcium chloride solution: 0.1831 g of calcium chloride was placed in a 25 mL beaker, and 20 g of deionized water from which carbon dioxide had been removed was added. Ultrasonication was performed for 10 min to obtain a calcium chloride solution.

[0047] (3) Preparation of precursor bulk CSH sol: Calcium chloride solution was added to the sodium silicate mixed solution, heated to 70°C in an oil bath at 1200 rpm and stirred for 6 h until the solution turned white. After the solution cooled to room temperature (24°C), ammonia water was added to the flask to adjust the pH to 12, and the mixture was collected by centrifugation to obtain a white bulk CSH sol.

[0048] (4) Powder sample preparation: The precursor bulk CSH sol is placed in a freeze drying oven, the freeze drying temperature is set to -40 °C, and the drying time is 12 h. After freeze drying, a bulk calcium silicate hydrate material with direct carbon capture performance can be obtained.

[0049] In the block direct carbon capture material CSH prepared in this example, the mass percentage of CTAB in the total solvent system is 0.005 g / mL, and the molar percentage of CSH in the total solvent system is 1 mmol / L. Therefore, the block calcium silicate hydrate material is recorded as CSH-0.005.

[0050] The bulk calcium silicate hydrate material prepared in this example was analyzed by transmission electron microscopy, and the results were as follows: Figure 1 As shown in b. Figure 1 From the TEM image in middle b, it can be seen that the CSH prepared using CTAB with a concentration of 0.005 g / mL is in block form.

[0051] Example 3

[0052] The experimental process was the same as that of Example 1, except that the amount of CTAB was changed to 0.4 g, 0.5 g, 0.6 g, and 0.8 g to prepare four groups of calcium silicate hydrate materials with a mass percentage of CTAB in the total solvent system of 0.010 g / mL, 0.0125 g / mL, 0.015 g / mL, and 0.020 g / mL, respectively. They were recorded as CSH-0.01, CSH-0.0125, CSH-0.015, and CSH-0.02, respectively.

[0053] Transmission electron microscopy analysis was performed on the four groups of calcium silicate hydrate materials with CTAB dosages of 0.010 g / mL, 0.0125 g / mL and 0.015 g / mL. The results are as follows: Figure 1 As shown in c, d and e. Figure 1 It can be seen from the figure that the CSH with a larger block size was formed when the CTAB concentration was 0.01 g / mL, and the CSH with sheet-like aggregates and rods was formed when the CTAB concentration was 0.015 g / mL. The CSH had a hollow structure, but the cavity structure was not connected. When the CTAB concentration was 0.0125 g / mL, the CSH gradually formed rods wrapped in the block, which was a transition state between block and rod.

[0054] The carbonization performance of the calcium silicate hydrate nanomaterials prepared with CTAB dosages of 0.0125 g / mL and 0.020 g / mL in Example 1, Example 2, Comparative Example 1 and Example 3 was tested (the carbon dioxide incubator selected for the test experiment was the Thermo3111 model, the setting mode was a carbon dioxide concentration of 0.3% and a temperature of 24°C). The specific test process is as follows: 70 mg of the calcium silicate hydrate material was placed in a carbon dioxide incubator and tested under the above conditions for 7 days (d). Three groups of parallel samples were tested. The results are as follows: Figure 2 shown.

[0055] Depend on Figure 2 It can be seen that the calcium silicate hydrate material (CSH-0) prepared in Comparative Example 1 without CTAB and carbonized for 7 days in an environment with a carbon dioxide concentration of 0.3% had a water content of 4.37%, a CTAB content of 0%, and a carbonization content of 22.59%. The rod-shaped calcium silicate hydrate material (CSH-0.005) prepared in Example 2 with a CTAB dosage of 0.005 g / mL and carbonized for 7 days in an environment with a carbon dioxide concentration of 0.3% had a water content of 3.59%, a CTAB content weight loss of 3.74% as determined by DTG data, and a carbonization content of 24.98%. The rod-shaped calcium silicate hydrate material (CSH-0.0125) prepared in Example 3 with a CTAB dosage of 0.0125 g / mL and carbonized for 7 days in an environment with a carbon dioxide concentration of 0.3% had a water content of 3.90%, a CTAB content weight loss of 7.14% as determined by DTG data, and a carbonization content of 25.69%. In Example 3, the rod-shaped calcium silicate hydrate material (CSH-0.02) prepared with a CTAB dosage of 0.020 g / mL had a water content of 3.10% after carbonization for 7 days in an environment with a carbon dioxide concentration of 0.3%, a TAB content of 18.54% by weight loss as judged by DTG data, and a carbonization content of 26.46%. In Example 1, the rod-shaped calcium silicate hydrate material (CSH-0.025) prepared with a CTAB dosage of 0.025 g / mL had a water content of 3.06% after carbonization for 7 days in an environment with a carbon dioxide concentration of 0.3%, a CTAB content of 19.88% by weight loss as judged by DTG data, and a carbonization content of 31.86%.

[0056] By comparison Figure 2 It can be seen that the rod-shaped or block-shaped calcium silicate hydrate materials prepared using CTAB have lower water content and higher carbonization ratio due to the increase in specific surface area due to changes in the nanostructure, indicating that the rod-shaped or block-shaped calcium silicate hydrate materials prepared using CTAB have better carbon capture effect than common flake materials under low carbon dioxide concentrations; during the carbonization process, the rod-shaped or block-shaped calcium silicate hydrate materials prepared using CTAB maintain a stable rod-shaped morphology, showing strong stability, which is the direct reason for ensuring the carbon capture effect.

[0057] This study modifies the reaction rate by adjusting the amount of CTAB added and selecting a higher molar amount of CSH in a 40mL solvent system, thereby altering its nanostructure and affecting the direct carbon dioxide capture ratio within the same amount of CSH. Notably, the optimized synthesis system has resulted in pure CSH with a higher carbon capture efficiency than currently reported commercial materials.

Claims

1. A calcium silicate hydrate nanomaterial, characterized in that: The calcium silicate hydrate nano material comprises solute calcium silicate hydrate and a total solvent system, wherein the total solvent system comprises hexadecyltrimethylammonium bromide, wherein the molar percentage of the calcium silicate hydrate to the total solvent system is 0.8-1.2 mmol / mL, and the solid-liquid ratio X of the hexadecyltrimethylammonium bromide to the total solvent system is 0<X≤0.030 g / mL.

2. The calcium silicate hydrate nano material according to claim 1, characterized in that: The calcium silicate hydrate nano material is in the shape of rods or blocks.

3. The calcium silicate hydrate nano material according to claim 1, characterized in that: When the solid-liquid ratio X of hexadecyltrimethylammonium bromide to the total solvent system is 0.0125<X≤0.030 g / mL, the hydrated calcium silicate nanomaterial is in rod shape.

4. The calcium silicate hydrate nano material according to claim 1, characterized in that: When the solid-liquid ratio X of hexadecyltrimethylammonium bromide (CTAB) to the total solvent system is 0<X<0.0125 g / mL, the hydrated calcium silicate nanomaterial is in block form.

5. A method for preparing the calcium silicate hydrate nanomaterial according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding sodium silicate and CTAB to a solution from which carbon dioxide has been removed, dispersing the solution under ultrasonication, and heating and stirring the solution under nitrogen protection to obtain a sodium silicate mixed solution; (2) adding CaCl2 to the sodium silicate mixed solution and heating to reflux for reaction; (3) adding ammonia water to the solution obtained in step (2) to adjust the pH value, collecting the precipitate by centrifugation, and freeze-drying to obtain a hydrated calcium silicate material.

6. The preparation method according to claim 5, characterized in that: In step (1), the solution is water or a solution containing water, the ultrasonic dispersion time is more than 10 minutes, and the heating and stirring is heated to 50-80° C. and stirred at 800-1200 rpm for more than 0.5 hour.

7. The preparation method according to claim 5, characterized in that: In step (2), the CaCl2 added is solid CaCl2 or a CaCl2 aqueous solution from which carbon dioxide has been removed, and the molar ratio of CaCl2 to sodium silicate is 1 to 2:

1.

8. The preparation method according to claim 5, characterized in that: In step (2), the heating reflux reaction is carried out at 60-80° C. and 800-1200 rpm for 4-8 hours.

9. The preparation method according to claim 5, characterized in that: In step (3), the pH is adjusted to 11 to 14, the freeze-drying temperature is -30 to -50°C, and the freeze-drying time is 6 to 12 hours.

10. Use of the calcium silicate hydrate nanomaterial according to any one of claims 1 to 4 in direct carbon capture.

Citation Information

Cited By

  • Calcium silicate / nanocellulose composite membrane for water treatment and preparation method thereof

    CN119869466A